In the Eye of the Beholder: Exploring Variations in the Perceptions of Pornography. Issue 6 (23rd July 2016) - Willoughby, Brian J.; Busby, Dean M.
Abstract : While many studies have explored the correlates and outcomes associated with pornography use, the measurement of such use has relied heavily on self-definitions of pornography from research participants, and little is known regarding how individuals define pornography for themselves. Using a diverse sample of 2, 089 individuals sampled from the online MTurk Web site, participants were asked to rate whether they felt 20 different examples of sexual media were pornography. Differences by gender, religious attendance, marital status, and pornography use patterns were explored. Results suggested significant variation across the sample in how specific examples of sexual media were perceived. In addition, response profiles significantly differed by gender, religious attendance, marital status, and use of pornography. Implications for the measurement of pornography are discussed.